DISC1: Structure, Function, and Therapeutic Potential for Major Mental Illness - Soares, Dinesh C. (American Chemical Society, 2011)
[Image: see text] Disrupted in schizophrenia 1 (DISC1) is well established as a genetic risk factor across a spectrum of psychiatric disorders, a role supported by a growing body of biological studies, making the DISC1 protein interaction network an attractive therapeutic target. By contrast, there is a relative deficit of structural information to relate to the myriad biological functions of DISC1. Here, we critically appraise the available bioinformatics and biochemical analyses on DISC1 and key interacting proteins, and integrate this with the genetic and biological data. We review, analyze, and make predictions regarding the secondary structure and propensity for disordered regions within DISC1, its protein-interaction domains, subcellular localization motifs, and the structural and functional implications of common and ultrarare DISC1 variants associated with major mental illness. We discuss signaling pathways of high pharmacological potential wherein DISC1 participates, including those involving phosphodiesterase 4 (PDE4) and glycogen synthase kinase 3 (GSK3). These predictions and priority areas can inform future research in the translational and potentially guide the therapeutic processes.